They both die at the end [book club bag] - Silvera, Adam, 1990- (Harper, an imprint of HarperCollinsPublishers, 2017)
In a near-future New York City where a service alerts people on the day they will die, teenagers Mateo Torrez and Rufus Emeterio meet using the Last Friend app and are faced with the challenge of living a lifetime on their End Day.